Pengembangan Modul Matematika Materi Bangun Datar Berbasis Kearifan Lokal Lembata NTT pada Siswa Kelas IV SD - Ana Endang P Kusumawati; Andri Anugrahana (Departement of Mathematics Education, 2024)
This research was motivated by the absence of a mathematics learning module for flat building materials based on local wisdom in Lembata, NTT, which was intended for fourth grade elementary school students. This research aims to develop a mathematics module for flat building materials based on local wisdom in Lembata NTT for fourth grade elementary school students, to determine the quality and implementation of the mathematics module.The research method used in this research is Research and Development (R&D). This research was carried out involving three validators, two teachers for needs analysis, and 10 students who were subjects in the trial process of a mathematics learning module with flat building materials based on local wisdom in Lembata, NTT. Observation and interviews are data collection techniques used in this research. Data analysis uses qualitative analysis and also quantitative analysis. The results of the research are (1) The ADDIE development model was used in developing a mathematical module for flat building materials based on local wisdom in Lembata NTT for fourth grade elementary school students. (2) The quality of the mathematics module on a Likert scale of 1-4 is included in the